PKM MENJAGA KESEHATAN FISIK DAN MENTAL PADA JURNALIS RADAR KEDIRI - Rinawati, Fajar; Fawzi, Alfian; Kurniasari, Dhita; Irawan, Hengky (Universitas Kadiri, 2024)
The life of a journalist is a life full of challenges, so it requires good physical and mental health. Therefore, there is a need for regular health checks and providing education, not only physical health but also mental health. The aim of this activity is to carry out community service activities for journalists regarding improving physical and mental health. The method used is the direct implementation method at the Radar Kediri Office. The number of participants was 31 people. The activities carried out consist of three stages, namely preparation, implementation and evaluation. The results obtained were that 36% had prehypertension, 26% had prediabetes and journalists were very enthusiastic about demonstrating again the stress management that was taught. This activity is really needed to improve the performance of journalists, because their lives require excellent health.